2009
DOI: 10.1051/limn/2009011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wastewater treatment plant pollution on in-stream ecosystems functions in an agricultural watershed

Abstract: -We studied the effect of point-source and non-point-source pollution on the retention capacity of the stream and its link with the metabolic state (primary production and respiration) and invertebrates assemblages in a third order Mediterranean stream. Two experimental sites were chosen: one in the upper part of the catchment (Monte´gut site) characterized by low concentrations in nitrate and phosphate and one in the lower part of the catchment (Le´zat site) characterized by high nitrate and phosphorus concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…About 93% and 99% of metolachlor and trifluralin respectively entering the stream network does not reach the outlet, suggesting high deposition (discussed above) and degradation in stream water. The latter would be consistent with the carbon consumption by river biota shown by Sánchez-Pérez et al [55] on a similar catchment of Gascogne.…”
Section: Long-term Pesticide Exportation Balance At Outletsupporting
confidence: 91%
“…About 93% and 99% of metolachlor and trifluralin respectively entering the stream network does not reach the outlet, suggesting high deposition (discussed above) and degradation in stream water. The latter would be consistent with the carbon consumption by river biota shown by Sánchez-Pérez et al [55] on a similar catchment of Gascogne.…”
Section: Long-term Pesticide Exportation Balance At Outletsupporting
confidence: 91%
“…These variables were related to sampling stations I6 and F6, which received inputs from the city of Huesca. Previous studies have reported that the primary source of P and NH 4 + -N are the urban inputs (Mendiguchía et al 2007;Neal et al 2000;Sánchez-Pérez et al 2009) and similarly for the case of NO 2 − -N (Martín-Queller et al 2010). Brainwood et al (2004) also observed that urban basins were highly correlated with NH 4 + ions and reactive PO 4 3− -P. Perona et al (1999) considered that in spring and summer, presence of holiday-makers leads to a high population density in the residential buildings and recreation areas influencing the nutrient content of the river.…”
Section: Spatiotemporal Variability Of Water Quality During Irrigatiomentioning
confidence: 85%
“…() and applied by Ruggiero, Solimini, and Carchini () and Sánchez‐Pérez et al. (). The estimation of the stream nutrient retention rate for NO 3 − ‐N was made on each sampling date with a solute addition of a known quantity of nutrient (NO 3 − ‐N) into the stream.…”
Section: Methodsmentioning
confidence: 99%